Methylene blue as a diagnostic aid in the early detection and screening of oral cancers and precancerous lesion. - Akmal, Nimra; Ibrahim, Muhammad Wasim; Malik, Numrah Shakeel; Aman, Nadia; Hanif, Maidah; Geelani, Rabia Rahat (Journal of Postgraduate Medical Institute, 2025)
Objective: to assess the reliability and sensitivity of in vivo methylene blue staining as a diagnostic tool for screening of oral malignant and premalignant lesions. Methodology: The study was conducted at oral and maxillofacial surgery department Foundation University College of Dentistry & Hospital, Islamabad, from October 2023 to December 2024. The screening for oral cancers and precancerous lesions was conducted on 77 patients. Clinical data on patients’ gender, age, followed by a systematic oral examination to clinically diagnose suspicious lesions on routine examination. Chair side Methylene blue dye uptake was compared with Biopsy report (Gold standard). Results: Out of 77 patients, 64 patients showed to be having oral cancer. The result indicated sensitivity of 93.8%, specificity of 53.8%, positive predictive value of 90.9%, negative predictive value of 63.6% and accuracy of 87%. Conclusion: Methylene blue staining is a reliable diagnostic tool for oral cancer screening, particularly for high-risk individuals. Its utility is especially significant in settings where access to advanced diagnostic tools may be limited, as it provides a cost-effective, non-invasive, and relatively simple method to improve diagnostic accuracy and prioritize individuals for further evaluation or biopsy. Keywords: Methylene blue, Dysplasia, Oral mucosa, Malignant lesion, Cancer